Kirtland Temple : The Biography of a Shared Mormon Sacred Space - Howlett, David James, 1978- (Book collections on Project MUSE., 2014)
The only temple completed by Mormon founder Joseph Smith, the Kirtland Temple in Kirtland, Ohio is contested by both the Latter-Day Saints and the Community of Christ denominations. The history of this building also includes the complex history of the two church branches.